A brief behavioural intervention to promote regular self-weighing to prevent weight regain after weight loss: a RCT - Daley, A; Jolly, K; Madigan, C; Griffin, R; Roalfe, A; Lewis, A; Nickless, A; Aveyard, P (National Institute of Health Research, 2019)
Background: Although behavioural weight loss treatments can be effective, long-term maintenance of this weight loss remains a critical challenge because the vast majority of people will regain their lost weight over time. The period after initial weight loss is the time when people are at the highest risk of weight regain. Objective: The primary aim of this study was to evaluate the effectiveness and cost-effectiveness of a brief behavioural intervention delivered by non-specialist call centre staff to promote regular self-weighing to prevent weight regain after intentional weight loss. Design: Randomised controlled trial. Setting: West Midlands, UK. Participants: Adults were recruited if they had attended a local authority-funded weight management programme and had lost ≥ 5% of their starting weight by the end of their weight loss programme. Interventions: The intervention group received three brief support telephone calls, delivered by non-specialist call centre staff (from a third-sector community organisation), that encouraged setting a weight maintenance target of ≤ 1 kg of weight gain from current weight, which was to be assessed by daily self-weighing and recording weight on a record card, together with regular text messages. Participants were asked to return to their weight loss plan if they gained > 1 kg above their target weight. The usualcare group received a standard weight maintenance leaflet, the infographic EatWell Plate and a list of useful websites pertaining to weight management. Main outcome measures: The primary outcome was the difference between the groups in mean weight change (kg) from baseline to 12 months. The secondary outcomes included the proportion of participants in each group who had regained < 1 kg in weight at the 3- and 12-month follow-up points. Results: A total of 813 potential participants were screened, 583 of whom were eligible and randomised (usual care, n = 292; intervention, n = 291). A total of 94% and 89% of participants completed follow-up at 3 and 12 months, respectively. At 12 months, the mean unadjusted weight change was +0.39 kg for the intervention group and –0.17 kg for the usual-care group, an adjusted difference of 0.53 kg [95% confidence interval (CI) –0.64 to 1.71 kg]. At 12 months, 134 (45.9%) and 130 (44.7%) participants regained ≤ 1 kg of their baseline weight in the usual-care and intervention groups, respectively (odds ratio 0.96, 95% CI 0.69 to 1.33). As the intervention was ineffective, we did not pursue a cost-effectiveness analysis.Conclusions: Brief behavioural telephone support delivered by non-specialist workers to promote target-setting and daily self-weighing and recording of weight does not prevent weight regain after intentional weight loss. Specifically, as target-setting and daily self-weighing did not increase conscious cognitive restraint, people may need more intensive interventions to promote the use of behavioural techniques that help people maintain lost weight. Trial registration: Current Controlled Trials ISRCTN52341938.